Virginiamycin via mineral supplementation and sward height in growing Nelore young bulls - Costa, João Paulo Ramos [UNESP] (2016)
The objective was evaluate the effect of virginiamycin (VM) via mineral supplement and two swards height (SH) on performance, blood metabolites, ruminal fermentation, ruminal microorganisms and microbial N production. The trial was divided in two experiments. Chapter 1: Eighty Nellore young Bulls (initial BW = 258 ± 15 kg) were blocked by weight and randomly assigned into 16 paddocks (5 animals/paddock) arranged in a 2 × 2 factorial design: mineral supplement without VM (WVM) or with VM and two SH [15 and 35 cm (15SH and 35SH, respectively)]. The animals receiving VM had higher ADG (P < 0.01). As expected, the 35SH had higher ADG (P < 0.01). VM had no effect on mineral supplement intake by BW (MSIBW) or mineral supplement intake by animal (MSIA) (P = 0.49 and P = 0.55, respectively) and 15SH showed a greater MSIBW and MSIA (P < 0.01 and P < 0.01, respectively). Blood albumin was greater in VM (P < 0.01) and tended to be greater (P = 0.07) in 35SH. The blood urea concentration tended to decrease in VM (P = 0.06) and was higher (P < 0.01) in 15SH. Plasma NEFA and calcium concentrations were greater (P = 0.007 and P = 0.038, respectively) in VM. Chapter 2: Twelve Nellore steer (initial BW = 334 ± 47) ruminally cannulated were used in three 4 × 4 balanced Latin square were assigned in the same treatment arrangement cited above. The DMI was greater (P < 0.01) in 15SH than in 35SH. Ammonia-N tended to be higher in VM (P = 0.07). None ruminal bacteria proportion were affected (P > 0.10), except R. flavefaciens that tended to increase in IV 35SH (P = 0.08), while total protozoa counts increased (P = 0.03) and the Entodinium genus tended to increase (P = 0.05) in VM. The VM increased uric acid (P < 0.01) and tended to increase the purines derivatives excretion (PD; P = 0.074), absorbed purines (AP; P = 0.07), microbial N flow (NMIC; P = 0.07) and the PD: creatinine ratio index [PDC index (P = 0.07)]. Therefore, the VM effect seems to be more related to increasing the N microbial flow to the intestine caused by incresing of ruminal protozoa than the ruminal fermentation.